AN UPDATE ON THE PERFORMANCE OF THE IN SITU 14C EXTRACTION LINE AT THE UNIVERSITY OF BERN. Issue 5 (26th October 2020) - Sliz, M U; Espic, C; Hofmann, B A; Leya, I; Szidat, S
ABSTRACT: We present the current performance of the in situ radiocarbon ( 14 C) extraction line at the University of Bern with an improved extraction and combustion system. After three major steps of improvement, the extraction of sample CO2 gas now takes place inside a platinum crucible, supported by an outer quartz-glass crucible. This setup allows us to operate the line as a closed system for several samples without breaking the vacuum. Measurements of procedural blanks and samples from our reference strewn field, Jiddat al Harasis 073, performed in our system all show a good reproducibility and, for the strewn field samples, consistency with published data. We describe each improvement step in detail, discussing the advantages and disadvantages of all tested setups. By sharing our knowledge, we aim to inform and prevent others from making the same or similar detours in establishing 14 C extraction systems for extraterrestrial samples.